Evaluation of how pandemic preparedness activities aided the response to influenza A (H1N1) pandemic in 2009: a qualitative analysis in seven countries within the WHO European Region - Hashim, Ahmed (2014)
Background: The 2009 influenza A (H1N1) pandemic was the first pandemic in the era of modern pandemic planning and preparedness. Although the mortality and morbidity caused by the pandemic was low compared with the previous pandemics, it gave the first opportunity for member states to implement an actual pandemic response reflecting on years of pandemic preparedness and planning. The objective of this study was to evaluate the usefulness of pandemic preparedness activities as well as to identify challenges and activities that require further improvement.